From Compliance to Cultural Outcomes: Rethinking Mandatory CSR in Bali - Antara Yasa, I Wayan Suka; Lie, Gunardi (Universitas Semarang, 2026)
This study aims to evaluate whether the legal framework governing Corporate Social and Environmental Responsibility (TJSL/CSR) in Bali has been effectively designed and implemented to maximize public and cultural welfare, or whether it remains confined to administrative compliance. Using a juridical-normative method informed by a utilitarian evaluation framework, this research examines the normative foundations of TJSL under the Company Law of 2007, Government Regulation No. 47 of 2012, and Law No. 15 of 2023 (ius constitutum), as well as their operationalization through Bali Provincial Regulation No. 8 of 2023 and Governor Regulation No. 46 of 2023 (ius operatum). The analysis demonstrates that, although the national legal framework provides sufficient authority for regional governments to coordinate and direct TJSL toward culture-based public welfare, its implementation in Bali remains predominantly input-oriented and administrative. The findings identify a significant utility gap, manifested in the absence of standardized cultural outcome indicators, outcome-based public reporting, independent verification mechanisms, and performance-based incentives or sanctions. As a result, TJSL policies have not been able to optimally translate corporate social resources into measurable benefits for key sectors of Balinese welfare, such as the strengthening of customary institutions, the preservation of ritual landscapes, and the transmission of traditional knowledge. The novelty of this study lies in its outcome-oriented evaluation of TJSL policy through a utilitarian lens, bridging normative legal analysis with public policy assessment. The study further proposes a direction for policy reconstruction that aligns TJSL implementation with cultural indicators mandated under Provincial Regulations No. 4 of 2020 and No. 5 of 2020, thereby repositioning TJSL as an effective instrument for cultural sustainability and public welfare rather than mere procedural compliance.